Current Problems of Modern Organization of Career Guidance for Students with Special Educational Needs at University - Nurgul, Toxanbayeva; Shynar, Ungarbayeva; Begalievna, Smatova Klara; Nazira, Sadykova; Karlygash, Sailinova; Beibit, Ayazbaeva; Nazirash, Zhubanazarova; Hapiza, Naubaeva (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
The article deals with the organization of career guidance for individuals with special educational needs in the Republic of Kazakhstan. This paper considers the professional orientation of young people with disabilities based on the theoretical analysis of the current state of career guidance organization. The authors pay special attention to the problem of effective career guidance activities, which largely depend on the comprehensive and consistent nature of these activities and involve all the aspects of the educational process.